Pertumbuhan dan Produktivitas Tebu pada Beberapa Paket Tata Tanam di Lahan Kering - ,, Djumali; Khuluq, Ahmad Dhiaul; Mulyaningsih, dan Sri (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTThe increasing demand on sugar and increasing land competition among agriculture comodities, urges improving sugar production through intensification programs. Planting arrangement was one of the intensification programs to increase sugar production. Hence the objective of the experiment was to evaluate planting arrangement in order to produce higher sugar yield. Research was carried out in Muktiharjo Research Station, Pati in January to October 2013 for plant cane (PC) and November 2013 to October 2014 for first ratoon cane (RC-1). Five packages of planting arrangement was evaluated in this study, they were (1) a single row CTC (distance inter row = from center to center) 110 cm + single seed, (2) single row CTC 130 cm + single seed, (3) double row CTC 50/135 cm + single seed, (4) double row CTC 50/170 cm + double seeds and (5) double row CTC 50/210 cm + double seeds, arranged in a randomized block design with three replications. A double row CTC 50/170 cm + double seeds planting arrangement produced the highest cane productivity, sugar yield and profit, i.e., 191.02 ton ha-1, 15.33 ton ha-1 and IDR 30,654,000,- ha-1, respectively for the PC whereas for the RC-1 was 177.36 ton ha-1, 12.43 ton ha-1, and IDR 30,897,000,- ha-1, respectively.Keywords: Double row, production, Saccharum officinarum, sugar yield